Photophysical Investigation of the Thermally Activated Delayed Emission from Films of m‐MTDATA:PBD Exciplex. (17th December 2013) - Graves, David; Jankus, Vygintas; Dias, Fernando B.; Monkman, Andrew
<x xml:space="preserve">Abstract</x> Understanding the delayed fluorescence mechanism behind the creation of emissive singlets from the non‐emissive triplets in exciplexes is vital for the fabrication of highly efficient blue fluorescent emitters, and subsequent white light applications. In this article we report the spectroscopic investigation of the exciplex formed between 4, 4′, 4′′‐tris[3‐methylphenyl(phenyl)amino]triphenylamine (m‐MTDATA) and 2‐(biphenyl‐4‐yl)‐5‐(4‐tert‐butylphenyl)‐1, 3, 4‐oxadiazole (PBD) in a 50:50 blended film. The mechanism behind extra singlet production in the blend is of E‐type nature, that is, "thermally activated" delayed fluorescence. The exciplex singlet‐triplet energy splitting is estimated to be around 5 meV, smaller than previously estimated at ≈ 50 meV. The absence of a well defined separation between prompt emission and emission components with very long lifetimes, >100 ns, is indicative of such a small exchange energy, and arises through multiple cycling between the resonant singlet and triplet manifolds before eventually being emitted from a singlet state. An observed redshift of the exciplex emission with time and increasing temperature is attributed to different exciplex species being formed between the m‐MTDATA and PBD molecules.